Inventory Model with Demand Dependant on Unit Cost- Input Parameters as Triangular Fuzzy Numbers - Kasthuria, R. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper considers an inventory model in which the shortages are backlogged and the demand is dependent on unit cost. An optimum value for average total cost is calculated by considering various input costs, lot size and maximum inventory under fuzzy environment. The process of defuzzification is done by using the signed distance method. Numerical example and sensitivity analysis is given for calculating both crisp and fuzzy values of the total cost.